Development Model of Traditional Ritual Festivalization as Cultural Tourism Attraction in Padang Panjang City, West Sumatra - Siti Ivadhea Harrisa; Yohanes Kristanto; I Made Sendra; Rahmad Oscar Ridho (Pelopor Publikasi Akademika, 2023)
Traditional rituals were part of the daily life of the Minangkabau and Mentawai indigenous peoples in the past. Since the arrival of Islam, the understanding that has developed in Minangkabau society is